ANALISIS DETERMINAN KESEMPATAN KERJA DAN KEMISKINAN PADA KABUPATEN/KOTA DI SUMATERA BARAT - Ahmadizon, Ahmadizon; Aimon, Hasdi (Universitas Negeri Padang, 2020)
Abstract : This research focuses on analyzing and knowing the effect of jobopportunities and poverty on Regencies/Cities in West Sumatra. This research isdescriptive and inductive. The data used in this study is secondary data with datacollection using panel data obtained from BPS West Sumatra Province 2013-2019period with 19 districts / cities in West Sumatra. This study analyzed using asimultaneous equation model (simultaneous equation regression model). Theresults of this study conclude that (1) Government investment has an insignificantand positive impact on employment opportunities, private investment has asignificant and positive impact on opportunities, economic growth has nosignificant effect and has a negative impact on employment opportunities. (2)Private investment has an insignificant and positive impact on poverty, economicgrowth has a significant and positive impact on poverty, education has asignificant and negative impact, while job opportunities have an insignificant andnegative impact on poverty in Regencies/Cities in West Sumatra 2013-2019.Keywords : Government Investment, Private Investment, Economic Growth,Education, Job Opportunities, Poverty.